Development of Online Indonesian Language Teaching Materials for Foreign Speakers for level 1 learners - Helmi Muzaki; Gatut Susanto; Didin Widyartono; Ilham Aksani; Pensri Panich (Indonesian Language Education and Literature, 2024)
The aims of this research is to produce bold Indonesian language teaching materials for Foreign Speakers (BIPA) for BIPA 1 students. This research uses a 4D model development model, namely defining, designing, developing and disseminating. The characteristics of the resulting teaching materials consist of 10 lesson units that can be used for learning BIPA 1 in bold. Learning topics are adapted to the BIPA 1 curriculum and relate to everyday life. These topics include letters and numbers, introductions, greetings, people closest to you, question words, simple sentences, mention of time in Indonesia, adjectives and basic expressions. The variety of Indonesian used in this open material varies between formal and informal according to the situation being discussed. Based on feasibility tests on aspects of graphics and organization, presentation, content, language and cultural values contained in the teaching materials, it can be concluded that the BIPA 1 darts teaching materials are suitable for use by BIPA 1 students.Pengembangan Bahan Ajar Bahasa Indonesia bagi Penutur Asing Secara Online untuk Pembelajar Tingkat 1Penelitian ini bertujuan untuk menghasilkan bahan ajar Bahasa Indonesia bagi Penutur Asing (BIPA) daring bagi pemelajar Tingkat 1. Penelitian ini menggunakan model pegembangan model 4D yaitu define, design, development, dan disseminate. Karakteristik bahan ajar yang dihasilkan terdiri atas 10 unit pelajaran yang dapat digunakan untuk pembelajaran BIPA 1 secara daring. Topik pembelajaran disesuaikan kurikulum BIPA 1 dan berkaitan dengan kehidupan sehari-hari. Topik-topik tersebut diantaranya huruf dan angka, perkenalan, salam sapaan, orang terdekat, kata tanya, kalimat sederhana, penyebutan waktu di Indonesia, kata sifat, dan ungkapan dasar. Ragam bahasa Indonesia yang digunakan dalam bahan ajar ini ragam formal dan informal disesuaikan dengan situasi yang dibahas. Berdasarkan uji kelayakan terhadap aspek kegrafikaan dan organisasi, penyajian, isi, bahasa, dan nilai budaya yang terkandung dalam bahan ajar dapat disimpulkan bahwa bahan ajar daring BIPA 1 ini layak digunakan oleh pebelajar BIPA 1.